Hypothalamic Menin regulates systemic aging and cognitive decline - Leng, Lige; Yuan, Ziqi; Su, Xiao; Chen, Zhenlei; Yang, Shangchen; Chen, Meiqin; Zhuang, Kai; Lin, Hui; Sun, Hao; Li, Huifang; Xue, Maoqiang; Xu, Jun; et al. (PLOS Biology, 2023)
This study reveals a role for hypothalamic Menin in organismal aging in mice, finding that Menin expression decreases in hypothalamic neurons during aging; mimicking this decrease induces premature aging phenotypes, while restoring Menin expression in the hypothalamus of aged mice ameliorates cognitive and systemic features of aging.